THE IMPLEMENTATION OF MIND MAPPING STRATEGY TO TEACH WRITING IN IELTS PREPARATION CLASS - Pratiwi, Damar Isti; Hartono, Rudi (English Education Journal, 2016)
This study is aimed to investigate the implementation of mind mapping strategy to teach writing in IELTS preparation class. It was a descriptive qualitative study on 20 students of IELTS preparation classes. Those students were divided into 6 classes based on their level after taking IELTS placement test. There were 3 teachers who taught 2 classes each. The data were collected by using classroom observations, studentsâ questionnaire, teachersâ interview, and document analysis. The present study revealed four results. First, mind mapping strategy was implemented by grouping the visual data to find out main trends, large increase or decrease, consistent direction and the relationship between modes and percentages in task 1; whereas in task 2, it was implemented by building studentsâ critical thinking to list main ideas which later on give supporting details for each main idea. Second, the students enjoyed teaching learning process through mind mapping strategy which resulted in passing guarantee program of having score improvement minimum 1 point, improved their analysis of data, enlarged their knowledge in academic writing topic, built their critical thinking and managed time well. Third, the problems during the implementation of those two strategies were teachersâ schedule, studentsâ activities at school before joining IELTS preparation class, time management, repetition ideas and phrases, laziness and boredom, and also illegible hand writing. Fourth, the solutions were: managing teachersâ and studentsâ schedule well, doing the test in time as instructions, reading many articles related with IELTS writing to broaden studentsâ knowledge, giving free writing, and practicing more..